2021
DOI: 10.1007/s10763-021-10222-w
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Lockdown: Parent Perspectives on Home-learning Mathematics During COVID-19 Lockdown

Abstract: During the COVID-19 pandemic, many parents suddenly had to assume responsibility for their children’s learning at home. Research conducted before the pandemic showed that mathematics homework is often unsuccessful or stressful for both parents and children and that tension exists between home and school in the learning of mathematics. Understanding parents’ experience of home-learning mathematics during lockdown has implications for positive learning relationships between home and school in the future. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…HW2.1 explained that learners were “unable to teach themselves [and] most times it was incorrect, thus [it was] challenging as a teacher to ‘unteach’ that incorrect method”. This issue echoes challenges noted by Darragh and Franke ( 2021 ) discussed earlier.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…HW2.1 explained that learners were “unable to teach themselves [and] most times it was incorrect, thus [it was] challenging as a teacher to ‘unteach’ that incorrect method”. This issue echoes challenges noted by Darragh and Franke ( 2021 ) discussed earlier.…”
Section: Resultssupporting
confidence: 74%
“…Mathematics homework has not been a regular practice of learners in low SES schools in the Eastern Cape (Graven, 2018 ). Darragh and Franke ( 2021 , p. 1) found that “mathematics homework is often unsuccessful or stressful for both parents and children and…tension exists between home and school in the learning of mathematics” and the quality of interaction between parents and learners in mathematics is influenced by parental mathematical ability. They note that changes in mathematics curricula and pedagogies mean parents are less able to draw on their own experience of learning when assisting their children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One would expect that the effects both of school closures in general and of particular distance learning techniques would vary not only with home resources but with a variety of aspects of parental and child characteristics, and with home-school relationships. For example, Darragh and Franke (2021) found that a sample of New Zealand parents had very varied perspectives on homelearning of mathematics during lockdown. 35.5% were positive; 29.9% were negative, 29.5% gave mixed responses and 5.24% were neutral.…”
Section: Discussionmentioning
confidence: 99%
“…One would expect that the effects both of school closures in general and of particular distance learning techniques would vary not only with home resources but with a variety of aspects of parental and child characteristics, and with home-school relationships. For example, Darragh & Franke (2021)) found that a sample of New Zealand parents had very varied perspectives on home-learning of mathematics during lockdown. 35.5% were positive; 29.9% were negative, 29.5% gave mixed responses and 5.24% were neutral.…”
Section: Discussionmentioning
confidence: 99%